Profil Kelainan Radiologi pada Remaja dengan Skoliosis - Widjaya, Inge Friska; Firmansyah, Yohanes; Nathaniel, Fernando; Wijaya, Dean Ascha (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Scoliosis is a type of spinal abnormality characterized by a lateral deviation of more than 10 degrees to the right or left. It affects 1-3% of children in the at-risk population, particularly those aged between 10 to 16 years. The main purpose of this research is to examine the radiological characteristics of scoliosis in teenagers using imaging (Spinal X-ray) at Royal Taruma Hospital. The sample for this study was selected using total sampling criteria from medical records gathered during the period from January to June 2023. The variables analyzed include age, gender, and the radiological features of scoliosis. The data was presented descriptively. Out of the 25 respondents, the average age was 15 years, with females comprising 88% of the participants. Most respondents (80%) exhibited a combination of dextroscoliosis and levoscoliosis. The median Cobb angle measurement for dextroscoliosis was 24 degrees, while for levoscoliosis, it was 26.5 degrees, both indicating moderate scoliosis. The curvature lesions for dextroscoliosis generally started at T5, and for levoscoliosis, they began at T12, with both types of scoliosis commonly ending at the level of L4. Keywords : Scoliosis, Spinal X-ray, Teenager  ABSTRAK Skoliosis merupakah salah satu bentuk kelainan tulang belakang dengan deviasi lateral lebih dari 10 derajat ke kanan atau ke kiri. Skoliosis mempengaruhi 1-3% anak-anak dalam populasi berisiko yaitu mereka yang berusia 10-16 tahun. Penelitian ini bertujuan untuk mengetahui profil kelainan radiologi pada remaja dengan skoliosis berdasarkan pemeriksaan radiologi (X-Ray Spine) di RS Royal Taruma yang dipilih sesuai kriteria secara total sampling menggunakan data rekam medis pada periode waktu Januari – Juni 2023. Variabel yang digunakan dalam penelitian ini yaitu usia, jenis kelamin, dan gambaran radiologi skoliosis. Data disajikan dalam bentuk deskriptif. Dari 25 responden, rerata usia adalah 15 tahun, didominasi oleh perempuan pada 88% responden, dan didapatkan kombinasi dextroskoliosis dan levoskoliosis pada 80% responden. Nilai median Cobb angel pada kelainan dextroskoliosis sebesar 24 derajat dan pada levoskoliosis sebesar 26,5 derajat dimana keduanya masuk dalam kategori moderate skoliosis. Letak lesi lengkungan pada dextroskoliosis dimulai dari T5 dan kelainan levoskoliosis dimulai dari T12, dan umumnya berakhir setinggi L4 baik pada dextroskoliosis maupun levoskoliosis. Kata Kunci: Remaja, Rontgen Tulang Belakang, Skoliosis